A new species of Scinax Wagler (Anura: Hylidae) from Mato Grosso, Brazil - Araujo-Vieira, Katyuscia; Valdujo, Paula Hanna; Faivovich, Julián (Zootaxa, 2016)
A new species of the Scinax ruber Clade is described from Municipality of Barra do Garças, State of Mato Grosso, Brazil. It is diagnosed by its size (SVL 29.4–35.4 mm in males); dorsum with a background that varies from light and dark gray to dark brown, with round and irregular dark blotches; hidden surfaces of thigh and shank light or dark brown, with lighter, large and irregular blotches (yellow in life); and nuptial pad that covers the medial margin of Metacarpal I, and obscures the posterior portion and the outer margin of the inner metacarpal tubercle. It is most similar with Scinax rupestris, from which it differs by having larger adult males; less developed nuptial pad; and hidden surfaces of thigh and light or dark brown, with lighter, large and irregular blotches (yellow in life). The new species occurs near the headwaters of permanent or temporary streams, where males call from vegetation or rocks at the margins of small streams.